Analisis Permasalahan Pembebasan Lahan pada Pekerjaan Pembangunan Jalan - Baneftar, Bobby S H; Thambas, Arthur H; Kumaat, Ellen J (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
An essential stage in road infrastructure development is land acquisition, which frequently causes project delays due to its complex legal, social, and economic challenges. This study aims to identify the factors that hinder the land acquisition process in the Manado Outer Ring Road (MORR) 3 Phase 4 Construction Project and to assess how these constraints affect the progress of construction activities. The research was conducted using a qualitative case study approach, with data collected through field observations, document reviews, and interviews. The findings indicate that delays in land acquisition are caused by discrepancies in legal status and land ownership, differing perceptions of compensation value, insufficient public socialization, and weak institutional coordination. These issues lead to disruptions in the construction schedule and potential increases in project costs. The study demonstrates that land acquisition necessitates a more cohesive strategy, facilitated by enhanced communication and community engagement, fortified land acquisition management frameworks, and precise verification of ownership data. The results indicate that there must be broader mitigation strategies to prevent similar challenges in future infrastructure projects.